Congenital erythropoietic porphyria with undescended testis - Sandeep Arora; Arun Kumar Harith; Neha Sodhi (Wolters Kluwer Medknow Publications, 2016)
Hereditary porphyrias are a group of metabolic disorders of heme biosynthesis pathway that are characterized by acute neurovisceral symptoms, skin lesions, or both. Congenital erythropoietic porphyria (CEP) is an extremely rare disease with a mutation in the gene that codes for uroporphyrinogen III synthase leading to accumulation of porphyrin in different tissues and marked cutaneous photosensitivity. We report a case of CEP with infancy onset blistering, photosensitivity, red colored urine, and teeth along with scarring. Examination revealed an undescended testis of the left side. Mutation analysis revealed mutation in the uroporphyrinogen III synthase gene (UROS) resulting in c. 56 A > G (Tyr19Cys). The presence of undescended testis with a rare mutation in a case of CEP which itself is an extremely rare condition make the case interesting.